The administration of nasal drops in the “Kaiteki” position allows for delivery of the drug to the olfactory cleft: a pilot study in healthy subjects - Mori, Eri; Merkonidis, Christos; Cuevas, Mandy; Gudziol, Volker; Matsuwaki, Yoshinori; Hummel, Thomas (European archives of oto-rhino-laryngology, 2016)
Systemic treatment with corticosteroids shows therapeutic effects, few patients benefit from intranasal topical drug application, probably due to limited access of the drug to the olfactory epithelium. The aim of the present study was to investigate how drops distribute within the nasal cavity when the “Kaiteki” position is performed. Thirteen healthy volunteers participated. Subjects were lying on the side with the head tilted and the chin turned upward. Blue liquid was used to visualize the intranasal distribution of the nasal drops. The investigation was carried out using photo documentation thorough nasal endoscopy; the intranasal distribution of the dye was judged by two independent observers in both a decongested state and a natural state where no decongestants had been used. With regard to the main criterion of this study, using the “Kaiteki” position, nasal drops reached the olfactory cleft in 96 % of the decongested cases and 75 % of the cases who had not been decongested. However, this difference was not statistically different. Because the “Kaiteki” maneuver is not too difficult to perform, it is more likely that topical steroids can be helpful in cases of olfactory loss.